Analisis Resiko Kebakaran dan Dampaknya dengan Pemodelan ALOHA pada Pertamini X di Kramat Jati Tahun 2024 - Ayu Anggraeni Dyah Purbasari (Lembaga Pengembangan Kinerja Dosen, 2024)
Pertamini or mini gas station is a retail business of fuel oil such as pertalit and pertramak carried out by the community. The absence of strict regulations regarding safety has caused many fire incidents involving it. ALOHA modeling is a tool for analyzing fire risks and their impacts, so that it can be a consideration of vigilance for perpetrators and the surrounding community. The purpose of this study was to analyze the effects of fires and explosions at the Dukuh Pertamini gas station in 2024. This study is a quantitative descriptive study using ALOHA software. The results of the study showed that the storage tank could create a fire pool with a diameter of 10 meters. If this happens, a flash fire can occur up to a distance of 60 meters, the heat of which can be felt up to 150 meters from the center of the explosion.